Bilateral agreement for the period 2011-2013 LLP/programme: higher education (Erasmus) between Universidade Lusíada de Lisboa and Lycée de La Salle - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities shown below within the LLP/ programme. - Erasmus subject area: Accounting, Management.